OPTIMAL HARVEST TIME MODEL IN AQUACULTURE TO MAXIMIZE PROFIT - D. Wijayanto; F. X. Sugiyanto; D. Poerwono (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTThe purpose of this study was to develop the optimal harvest time to generate maximum profits in Aquaculture. This study used a model of von Bertalanffy length growth combined with the length-weight relationship and the mortality rate to estimate of fish biomass. Profit was calculated as total of revenue minus total of cost. Both the harvested biomass of fish and price of fish were determined as factors affected the revenue of aquaculture. The components of costs were cost of seed procurement, cost of feed procurement, cost of harvesting transportation and the daily cost. The daily cost of aquaculture in floating cages are cost of labour, cost of medicines, cost of energy, cost of assets depreciation, cost of supporting equipment and cost of maintenance assets that converted to IDR/day. Profit maximization was performed by derivative the equation of profit to aquaculture periods (first order condition), and its second derivatives was negative (second order condition). The research model was applied to the red Tilapia culture in floating cages at the Reservoir of Wadaslintang, Indonesia. The research results demonstrate that the model in this study can be used to estimate aquaculture periods (286 days) which can generates maximum profits.